RFID Implementation on Information Recording Systems of Deer - Jonathan Tyar Putro Wicaksono; Erdhi Widyarto Nugroho; FX Hendra Prasetya (Journal of Business and Technology, 2022)
Deer are animals that currently still have conservation status as protected animals. However, for the activities of breeding and caring for deer animals, they are allowed and given legal payment by the government. However, in practice, there is still a lot of illegal deer meat or the result of illegal hunting which is also sold in the Indonesian market. Recording of deer seed genealogy and legality of breeding is one way to differentiate between illegal and legal deer meat sellers. However, due to the manual form of recording, human errors often lead to errors in recording. Therefore we need an application that can handle manual recording coupled with the implementation of RFID on meat so that it is expected to facilitate the existing recording process. The purpose of this research is to create a deer recording system application that can assist users in making sales and purchasing transactions as well as checking the lineage of deer seeds using the implementation of RFID. The method applied is through the design of Use Case Diagrams, Entity Relationship Diagrams, flowcharts, and using the Laravel 7 framework with the application of MVC to produce a Deer Recording System (SRS) application aimed at helping breeders. After the application was generated, testing was carried out on 84 buyers and prospective buyers of deer meat in deer breeding in Kudus, and the results showed that the EE (convenience) and FC (facilities) variables had a significant correlation with the BI variable (desire to return).